Sexual well-being in patients with vulvar disease: results from a preliminary prospective matched case–control study. (November 2015) - Wylomanski, Sophie; Bouquin, Réjane; Hanf, Matthieu; Winer, Norbert; Dréno, Brigitte; Rouzier, Roman; Quéreux, Gaëlle
Abstract: Introduction: Only a few studies have focused on the description of sexual well-being in patients with vulvar disease (VD). The aim of this study was to test the hypothesis that VD patients have an overall impaired sexual well-being that varies depending on the type of VD. Study design: An observational, prospective, single center and 1:1 matched case–control study was conducted in Nantes University Hospital (France). All new patients attending the specific consultation for VD between June 2011 and January 2013 were included. A control group was randomly selected from women who had a scheduled consultation for gynecologic follow-up. A validated French version of the Female Sexual Function Index (FSFI) was used. This self-administered questionnaire was distributed to all case and control women. VD was classified into 4 groups: inflammatory, (pre)malignant, infectious, and other VD. Descriptive statistics and multivariate mixed analyses were performed. Results: Seventy-two VD patients and seventy-two control women completed the FSFI questionnaire. The median FSFI score was 21.1 in the VD patients versus 28.1 in the control patients. In the multivariate analysis, the FSFI score was significantly decreased by an average of 4.5 points ( p  = 0.003) in the VD patients. On the FSFI subscores, VD had significant impacts on items related to "arousal", "pain", "lubrication", "satisfaction", and "desire". When comparing the VD groups, the total FSFI score seemed lower for (pre)malignant VD. Conclusion: This preliminary study showed that VD patients had an impaired sexual well-being.